Applied data communications : a business-oriented approach - Goldman, James E. (New York : John Wiley & Son, Inc., 1995)
Intended for undergraduate and MBA courses in data communications for business managers, this study offers an emphasis on business problem-solving. Multimedia network software is available to accompany the text.
The Current State of the Data Communications Industry -- Introductory Concepts -- Personal Computer Connectivity; Local Area Networks (LANs) and LAN Look-Alikes -- Local Area Networking Technology -- Connecting LANs: Inter-Networking -- Basic Principles of Wide Area Networking -- Emerging Wide Area Networking Services and Technology -- Enterprise Networking and Client/Server Architectures -- Voice Communications and Voice/Data Integration -- Networking Aspects of Videoconferencing, Imaging, and Multimedia -- The Network Development Life Cycle -- Where Do We Go from Here? -- Trends to Watch.
Includes bibliographical references and index.
Keywords: ELECTRONIC DATA INTERCHANGE